Student's Mistakes Awareness in Process of Negotiation of Meaning Based on Student's Level Proficiency Level - Arpinda Syifaa Awalin; Syafi’ul Anam; Oikurema Purwanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to know students making mistakes during the negotiation process based on their level of proficiency. This study was conducted at one of a university in Surabaya. The case study is used to know the differences of student’s mistake awareness in different level proficiencies. The instruments of data collection were observation, audiovisual recording and interview. The source of data was student’s utterances. This study showed that every criterion has different mistakes that students made during the process of negotiation of meaning. The addition of student’s level proficiency influenced their mistakes awareness in process negotiation of meaning. Keyword: Case Study, Level of Proficiency, Mistake, Negotiation of Meaning